A high school gym-induced disease. Issue 12 (23rd January 2008) - Seitz, C S; Bröcker, E B; Trautmann, A
Abstract : Physical exercise may induce upper and lower airway symptoms such as rhinitis and asthma. Rhinitis symptoms are often neglected although runny nose and nasal congestion may interfere with performance of the affected individual. A detailed history regarding locality and time of symptoms is of most significance for taking the appropriate diagnostic measures and identifying, as in this case, an uncommon form of allergic rhinitis to airborne spores from moulds.